2019
DOI: 10.3390/app9235235
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin Hydrogel Film Based Chitosan–Alginate for Recurrent Aphthous Stomatitis

Abstract: Featured Application: This study highlights a novel application of α-mangostin hydrogel film based chitosan-alginate. α-mangostin has been known as an agent for oral cavity therapy. However, α-mangostin is difficult to be delivered directly to the site. This novel application of hydrogel film-based chitosan-alginate have the potential as carriers of α-mangostin for recurrent aphthous stomatitis therapy.Abstract: Many antiseptic drugs, local anaesthetics, and corticosteroids have been used for effective therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The diffraction pattern of α-M/HP-β-CD PM displayed the same peak with α-M/ at 5° and 14°, indicating that the crystallinity was still detectable. This intense peak disappeared in α-M/HP-β-CD CX, indicating that α-M was probably entrapped in the cavity of HP-β-CD [ 17 , 23 ]. The spectra indicated that the interaction between α-M and HP-β-CD probably formed a number of hydrogen bonds and changed the physical characteristic of the drug in the complex [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diffraction pattern of α-M/HP-β-CD PM displayed the same peak with α-M/ at 5° and 14°, indicating that the crystallinity was still detectable. This intense peak disappeared in α-M/HP-β-CD CX, indicating that α-M was probably entrapped in the cavity of HP-β-CD [ 17 , 23 ]. The spectra indicated that the interaction between α-M and HP-β-CD probably formed a number of hydrogen bonds and changed the physical characteristic of the drug in the complex [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a deacetylation process derived from chitin and is composed of d -glucosamine and N-acetyl- d -glucosamine units linked to β-(1→4) [ 38 , 39 , 40 ]. Chitosan is one of the possible drug carrier nanoparticles (NPs) because of its biodegradability and biocompatibility and displayed non- or minimal toxicity [ 41 ].…”
Section: Chitosan-based Nanoparticles Preparation and Modificationmentioning
confidence: 99%
“…The strong antioxidant activity in ulvan is able to make it a therapeutic agent [10,22,28,70] and in subsequent studies, the benefits of ulvan were investigated to have anti-inflammatory, anti-cancer, immunomodulatory, anti-hyperlipidemic, anti-bacterial, and anti-virus activities. Ulvan, which is composed most of polysaccharides, has the potential to be developed in biomedical formulations as polymers in hydrogel formulations [29]; this characteristic of ulvan polysaccharides is similar to that of alginate polymers [73]. Ulvan is also used in the field of tissue engineering for cartilage combined with poly (D-lactic acid) (PDLLA) [74].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Ulvan-based hydrogels can be used in cartilage tissue engineering [128]. Ulvan also contains polysaccharides that are similar to alginates, so it can be used as a hydrogel polymer [73]. Ulvan extracted from U. lactuca and chitosan extracted from Loligo forbesii squid-pen produced 98% carboxymethylated ulvan (CMU) and 87% carboxymethyl chitosan.…”
Section: Tissue Engineeringmentioning
confidence: 99%